Caring for aged people: The influence of personal resilience and workplace climate on 'doing good' and 'feeling good'. (20th February 2019) - McNeil, Nicola; Bartram, Timothy; Cregan, Christina; Ellis, Julie; Cooke, Fang Lee
Abstract: Aims: This study examines the impact of personal resilience on the well‐being of care workers and how perceptions of the quality of care provided and the social climate in the organization influences this relationship. We examine quality of patient care as both a mediating and outcome variable to better understand if 'doing good' (quality of care) leads to 'feeling good' (personal well‐being). Background: As an ageing population and the care for the older people has become an increasing challenge to many societies, developing and retaining a professional care workforce through effective management is vital in providing care services. Design: A cross‐sectional regression design was used in the study. Methods: In 2017 we surveyed care workers in 20 Australian aged care facilities. The sample consist of 194 usable questionnaires. Using regression techniques, we constructed an interaction term (resilience × social climate) and investigated its impact on well‐being (the outcome variable) and quality of care (the mediator variable). Results: Our results reveal that quality of care is important as an outcome variable particularly in a supportive climate where high personal resilience positively influences quality of care. Quality of care is also important as a mediating variable as it provides a conduit through which high personal resilience fosters well‐being, especially in a supportive climate. Our results support the argument that 'doing good' leads to 'feeling good'. Conclusion: These findings contribute to our appreciation of the important outcomes of resilience in the aged care context and its influence on perceived performance and carer well‐being. 摘要: 目的: 本研究探讨个人恢复力对护理人员幸福感的影响, 以及对护理质量和组织内社会氛围的认知如何影响这种关系。我们将患者护理质量作为中介变量和结果变量进行研究, 以更好地理解"做得好"( 护理质量)是否会导致"感觉好"( 个人幸福感)。 背景: 由于人口老龄化和对老年人的照顾已成为许多社会日益增加的挑战, 通过有效管理发展和留住专业护理人员对提供护理服务至关重要。 设计: 本研究采用横断面回归设计。 方法: 2017年, 我们对澳大利亚20家老年护理机构的护理人员进行了调查。样本包括194份可用问卷。利用回归技术, 我们构建了一个交互项(恢复力×社会气氛), 并研究了它对幸福感(结果变量)和护理质量(中介变量)的影响。 结果: 我们的研究结果表明, 护理质量作为一个结果变量非常重要, 特别是在支持性氛围中, 高个人恢复力对护理质量有积极影响。护理质量也是一个重要的中介变量, 因为它提供了一个管道, 通过高个人恢复力培养良好的生活, 特别是在支持性的氛围中。我们的研究结果支撑了"做好事会让人感觉良好"的观点。 结论: 这些发现有助于我们认识到老年护理中适应力的重要结果及其对感知绩效和护理人员幸福感的影响。